Comparative analysis of advanced dental implant materials for enhanced biocompatibility and mechanical stability - Lakkundi, Anand R; G J, Satish; H K, Madhusudhana; Gaitonde, V N (Edelweiss Applied Science and Technology, 2025)
Identification of the best dental implant materials is crucial to achieve high levels of biocompatibility, mechanical stability, and long-term patient satisfaction. The current study provides a comparative review of new materials used in dental implants, including titanium, zirconia, polyetheretherketone (PEEK), cobalt-chromium alloy, and graphene. The motivation for the study is the increasing need for implant materials that are biocompatible and possess high mechanical properties, which provide durability and comfort for patients. The strategy involves a comprehensive evaluation of the material properties of each, focusing on density, tensile strength, modulus of elasticity, and deformation under bite loading. Static structural integrity and stress distribution studies revealed that graphene has an extremely high tensile strength (130 GPa) and very low deformation (0.0002 mm), making it a highly promising material for use in high load-bearing conditions. These findings highlight graphene’s potential as a robust, biocompatible substitute for traditional materials, capable of enhancing implant longevity and performance.